Impact of commensal flora on periodontal immune response to lipopolysaccharide. Issue 10 (29th August 2018) - Fukuhara, Daiki; Irie, Koichiro; Uchida, Yoko; Kataoka, Kota; Akiyama, Kentaro; Ekuni, Daisuke; Tomofuji, Takaaki; Morita, Manabu
Abstract: Background: Commensal flora are involved in the appropriate development of the mature immune system. However, it is unclear how commensal flora contribute to immune responses against periodontal pathogens, including the response to lipopolysaccharide (LPS). The purpose of this study was to evaluate the expression of immune responses after topical application of LPS in germ‐free (GF) and specific‐pathogen‐free (SPF) mice. Methods: GF and SPF mice at 8 weeks of age were randomly divided into four groups each: a baseline group ( n = 4/group) and three experimental groups ( n = 6/group). Experimental groups received topical application of Porphyromonas gingivalis LPS (10 μg/μL) into the palatal gingival sulcus. Sampling was performed before LPS application (baseline) and at 3, 24, or 72 hours after LPS application. The numbers of neutrophils, CD4 +, and CD8 + T cells in periodontal tissue were evaluated by immunohistochemistry. Expression of genes encoding cytokines, chemokines, and a transcription factor was determined by real‐time PCR. Results: SPF mice, but not GF mice, showed an increased number of CD4 + T cells in the periodontal tissue at 3 hours after LPS application, compared with the number at baseline ( p < 0.05). Gene expressions of tumor necrosis factor‐α ( Tnf‐α ) and forkhead box protein p3 ( Foxp3 ) was also significantly higher in the SPF mice than in the GF mice at 3 hours after LPS application ( p < 0.05). The number of neutrophils peaked at 24 hours in both GF and SPF mice. Conclusions: LPS‐exposed SPF mice exhibited increases in the number of CD4 + T cells and in Tnf‐α and Foxp3 gene expression in periodontal tissue compared with LPS‐exposed GF mice.